11 Decades of Dissemination of Xi You Ji, Journey to the West: : A Study through Printing and Translation - Jiraphas, Charassri (Academic and Research Journal of Liberal Arts (Online), 2021)
The fiction of Xi You Ji, Journey to the West is a Chinese classical literature that had been broadly disseminated, through printing and translation, into many languages because of its aesthetic, imaginative, literary, and philosophical values. This article aimed to: 1) digest and analyze the printing in Thai versions of Xi You Ji, since the early 20th century to 2020 CE. 2) sort the translated Thai versions of Xi You Ji. 3) propose guidelines of studying Chinese classical literature through the study of dissemination. From the study, it was found that the comic versions of Xi You Ji had been popular in the 21st century. For Thai translation from the original Chinese version, three Thai versions were found: two non-literal and one literal. Also, new compositions, both fiction and cartoons, from the widespread draft of translation in the 20th century were found.